Circadian rhythms have broad implications for understanding brain and behavior. (5th May 2014) - Silver, Rae; Kriegsfeld, Lance J.
Abstract Circadian rhythms are generated by an endogenously organized timing system that drives daily rhythms in behavior, physiology and metabolism. In mammals, the suprachiasmatic nucleus (SCN) of the hypothalamus is the locus of a master circadian clock. The SCN is synchronized to environmental changes in the light:dark cycle by direct, monosynaptic innervation via the retino‐hypothalamic tract. In turn, the SCN coordinates the rhythmic activities of innumerable subordinate clocks in virtually all bodily tissues and organs. The core molecular clockwork is composed of a transcriptional/post‐translational feedback loop in which clock genes and their protein products periodically suppress their own transcription. This primary loop connects to downstream output genes by additional, interlocked transcriptional feedback loops to create tissue‐specific 'circadian transcriptomes'. Signals from peripheral tissues inform the SCN of the internal state of the organism and the brain's master clock is modified accordingly. A consequence of this hierarchical, multilevel feedback system is that there are ubiquitous effects of circadian timing on genetic and metabolic responses throughout the body. This overview examines landmark studies in the history of the study of circadian timing system, and highlights our current understanding of the operation of circadian clocks with a focus on topics of interest to the neuroscience community.